2015
DOI: 10.1007/s11239-015-1245-z
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of dabigatran and rivaroxaban on platelet reactivity and inflammatory markers

Abstract: The new oral anticoagulants (NOACs) reduce stroke and systemic embolism in patients with non-valvular atrial fibrillation (AF), but dabigatran may increase risk of coronary ischemic events for unclear reasons. Thus, this study assessed the effects of dabigatran and rivaroxaban on platelet reactivity and inflammatory markers in patients with non-valvular AF. Patients with non-valvular AF planned to begin treatment with NOACs were included. Seventeen patients were prescribed dabigatran and ten rivaroxaban. Plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…Our data are in line with a report of Zemer-Wassercug et al who also failed to demonstrate any significant changes in platelet reactivity measured by multiplate-aggregation, platelet P-Selectin expression and plasma RANTES levels from baseline to at least 7 days on Rivaroxaban or dabigatran therapy [18]. Since the average life span of circulating platelets is 8-9 days, effects on megakaryocytes and mRNA derived platelet protein synthesis in response to cellular activation might have been missed in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in line with a report of Zemer-Wassercug et al who also failed to demonstrate any significant changes in platelet reactivity measured by multiplate-aggregation, platelet P-Selectin expression and plasma RANTES levels from baseline to at least 7 days on Rivaroxaban or dabigatran therapy [18]. Since the average life span of circulating platelets is 8-9 days, effects on megakaryocytes and mRNA derived platelet protein synthesis in response to cellular activation might have been missed in this study.…”
Section: Discussionsupporting
confidence: 93%
“…32,33 HMGB-1 is highly expressed in platelet-rich human coronary artery thrombi 34 and a key mediator of reciprocal communication between platelet and neutrophils, as well as monocytes facilitating formation of prothrombotic neutrophil extracellular traps and production of monocyte-derived tissue factor. 33 We found that P-selectin exposure was not affected by VLD rivaroxaban treatment, findings that are in line with previous studies 35,36 that both found no significant effect of rivaroxaban on platelet P-selectin expression and release. However, in the present study, we could show that platelet surface abundance of HMGB-1 was significantly reduced after treatment with VLD rivaroxaban pointing to a potential effect on thrombo-inflammatory processes triggered by platelets in patients with coronary artery disease.…”
Section: Discussionsupporting
confidence: 91%
“…Quercetin does not affect P-gp-mediated efflux, as reflected by a lack of effect on digoxin pharmacokinetics (39). We observed that isoquercetin significantly lowers soluble P selectin levels and that this is an activity not shared by other anticoagulants, such as warfarin, dabigatran, or rivaroxaban (40)(41)(42). P selectin binds to P selectin glycoprotein ligand-1 on the surface of leukocytes to promote the generation of tissue factor bearing microparticles and thrombus formation (43).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 93%